2001
DOI: 10.1126/science.1060438
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Native-Like Topology in a Denatured Protein in 8 M Urea

Abstract: Experimental methods have demonstrated that when a protein unfolds, not all of its structure is lost. Here we report measurement of residual dipolar couplings in denatured forms of the small protein staphylococcal nuclease oriented in strained polyacrylamide gels. A highly significant correlation among the dipolar couplings for individual residues suggests that a native-like spatial positioning and orientation of chain segments (topology) persists to concentrations of at least 8 molar urea. These data demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
521
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 586 publications
(555 citation statements)
references
References 21 publications
30
521
2
2
Order By: Relevance
“…Under denaturing conditions, the protein can still exhibit native conformational bias and retain a certain amount of residual native structures. Mounting experimental evidence [168,[195][196][197][198] supports residual native-like structural elements in the denatured state for a variety of proteins. Using residual dipolar coupling from NMR measurements, Shortle and Ackerman [195] showed that native-like topology persists under strong denaturing conditions as high as 8 M Urea for a truncated staphylococcal nuclease.…”
Section: Unfolded Protein Statesmentioning
confidence: 91%
See 2 more Smart Citations
“…Under denaturing conditions, the protein can still exhibit native conformational bias and retain a certain amount of residual native structures. Mounting experimental evidence [168,[195][196][197][198] supports residual native-like structural elements in the denatured state for a variety of proteins. Using residual dipolar coupling from NMR measurements, Shortle and Ackerman [195] showed that native-like topology persists under strong denaturing conditions as high as 8 M Urea for a truncated staphylococcal nuclease.…”
Section: Unfolded Protein Statesmentioning
confidence: 91%
“…Mounting experimental evidence [168,[195][196][197][198] supports residual native-like structural elements in the denatured state for a variety of proteins. Using residual dipolar coupling from NMR measurements, Shortle and Ackerman [195] showed that native-like topology persists under strong denaturing conditions as high as 8 M Urea for a truncated staphylococcal nuclease. By applying quasi-elastic neutronscattering on α-lactalbumin, Bu et al [196] demonstrated residual helical structure and tertiarylike interactions even in the absence of disulfide bonds and under highly denaturing conditions.…”
Section: Unfolded Protein Statesmentioning
confidence: 91%
See 1 more Smart Citation
“…The reversible denatured state of soluble proteins has been characterized as an ensemble of multiple conformations with a very low content of secondary and tertiary structure (Shortle and Ackerman 2001). Contrasting with the observed parallelism in the unfolding energetics between membrane and soluble proteins, helical membrane proteins seem to retain significant secondary structure in the unfolded states Roman et al 2010).…”
Section: The Thermally Induced Membrane Protein Denatured Statementioning
confidence: 99%
“…states [167]. Thus, while the rigid native-like core of the protein is formed, a significant fraction of amino acids in the flexible regions of the protein can exist in the unfolded state.…”
Section: Heat Capacity Of Metmyoglobinmentioning
confidence: 99%